Energy communities: engaging people and technologies in the future of energy [version 1; peer review: 1 approved, 2 approved with reservations] - Aggeliki Aggeli; Paula Jiménez Argumosa; Tatiana Loureiro; Julia Blanke; Blanca Barrios; Marta Arniani (Open Research Europe, 2022)
This is a summary of the clustering workshop at the Sustainable Places 2022 conference. The H2020 funded projects LIGHTNESS, HESTIA, LocalRES and CREATORS came together to shed light on the importance of engaging people and unlocking the potential of technologies to promote energy communities and meet the EU’s ambition of a joint net-zero emission of greenhouse gases by the year 2050. To ensure a people-centric, sustainable, just, and innovative energy future, citizens and experts must be brought into dialogue to co-design new ways of organising around energy.